2009
DOI: 10.1042/bj20090723
|View full text |Cite
|
Sign up to set email alerts
|

A survey of proteins encoded by non-synonymous single nucleotide polymorphisms reveals a significant fraction with altered stability and activity

Abstract: On average, each human gene has approximately four SNPs (single nucleotide polymorphisms) in the coding region, half of which are nsSNPs (non-synonymous SNPs) or missense SNPs. Current attention is focused on those that are known to perturb function and are strongly linked to disease. However, the vast majority of SNPs have not been investigated for the possibility of causing disease. We set out to assess the fraction of nsSNPs that encode proteins that have altered stability and activity, for this class of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 74 publications
4
47
0
Order By: Relevance
“…First, we found that the dynamic range of PKAR was diminished by K433E, a mutant that blocks PKM2 binding to phosphotyrosine peptides that catalyze the release of FBP (43), as well as S437Y, which inhibits the ability of FBP to displace these peptides (48). Our data also suggest that the direct phosphorylation of PKM2 at Tyr-105 shifts PKM2 to its inactive state by disrupting FBP binding, as Y105F, which blocks this phosphorylation event (47), also diminished PKAR dynamic range.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, we found that the dynamic range of PKAR was diminished by K433E, a mutant that blocks PKM2 binding to phosphotyrosine peptides that catalyze the release of FBP (43), as well as S437Y, which inhibits the ability of FBP to displace these peptides (48). Our data also suggest that the direct phosphorylation of PKM2 at Tyr-105 shifts PKM2 to its inactive state by disrupting FBP binding, as Y105F, which blocks this phosphorylation event (47), also diminished PKAR dynamic range.…”
Section: Discussionmentioning
confidence: 99%
“…To test this possibility we evaluated three PKM2 mutants that block 1) tyrosine phosphorylation of PKM2 (Y105F) (47), 2) PKM2 binding to endogenous phosphotyrosine peptides (K433E) (43), or 3) the ability of FBP to displace phosphotyrosine peptides (S437Y) (48). All three mutants decreased PKAR activation by glucose by Ն50% (Fig.…”
Section: Multi-and Single-chain Fret Biosensors Engineered Frommentioning
confidence: 99%
See 1 more Smart Citation
“…A blind test of both methods against experimental data for a small set of germ line SNPs occurring in a set of enzymes also shows a high level of agreement. 32 …”
Section: Introductionmentioning
confidence: 99%
“…A recent study examined 46 coding polymorphisms for 16 human enzymes with known three-dimensional structures and found that a high proportion (48%) of these natural variants results in altered thermal stability and, in some cases, catalytic efficiency or allosteric regulation (Allali-Hassani et al 2009). From the considerations discussed above, we speculate that altered thermostability leading to a phenotypic outcome may depend on factors such as the "strength" of the chaperone network in a given individual, influences by polymorphisms in chaperone or stress regulatory genes and imbalanced coexpression of chaperones and cochaperones, environmental influences and exposures to proteotoxic stresses, and the presence of other destabilized or misfolded proteins, particularly those acting in the same pathway or competing for the same chaperones (Fig.…”
Section: Natural Genetic Variation: Polymorphisms and Mutationsmentioning
confidence: 99%